PEMBERIAN KOMBINASI GLUKOSA:FRUKTOSA 50%:50% TERHADAP GLUKOSA DARAH SEBELUM DAN SETELAH AKTIVITAS FISIK SUBMAKSIMAL - Yohanis Manfred Mandosir (JURNAL OLAHRAGA PAPUA, 2013)
ABSTRACT : The purpose of this study was to determine the effect of different combinations of solutions of glucose: fructose 30%: 70% with a combination solution of glucose: fructose 50%: 50% of blood glucose levels before and after sub-maximal physical activity. Research to be done was quasi-experimental using the randomized pre-test and post-test design. Research subjects, amounting to 8 people aged 21-24 years were given two different treatments, namely K1 solution that will consume the combination of glucose: fructose 30%: 70% and K2 solution that will consume the combination of glucose: fructose 50%: 50%. Exercise in this study was sub-maximal ergocycle by pedaling a bicycle using 80% HR-max for 6 minutes. Measurement of blood glucose were performed by means of artificial Blood Glucose Meter with San Diego-American units of mg/dL. The data obtained was analyzed by descriptive statistics, normality test, paired samples test and independent samples test with a significance level of 0.05. Thus we can conclude that: (1) Increased blood glucose levels prior to the activity of the combination of glucose: fructose 30%:70% was not lower than the combination of glucose: fructose 50%:50%. (2). Decrease in blood glucose levels after activity on providing a combination of glucose: fructose 30%: 70% was not lower than the combination of glucose: fructose 50%:50%. Key word: combination glucose: fructose, glucose blood, sub-maximal physical activity